Learning as a family every day (8) (Journal of Parents and Teachers, 1996)
Poetry is presented as an essential form of communication and individual expression, where each person is part of this experience. The relevance of reading and interpreting poems is emphasized, connecting poetry with personal experiences. It is also emphasized that the word is a key component in poetic creation.
Keywords: poetry; communication; reading; expression